2022
DOI: 10.3390/ijerph19074307
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic Effects of Lead and Their Impact on the Expression of DNA Repair Genes

Abstract: Exposure to lead (Pb) continues to be a significant worldwide problem. Pb is a highly poisonous heavy metal affecting several organ systems in the body. Although Pb has been shown to be genotoxic to experimental animals and humans, the underlying mechanisms are still not understood. An indirect mechanism related to the inhibition of DNA repair systems by Pb has been suggested. Heavy metals can interfere with the activities of several proteins and gene expressions. Recent studies gathered in this review article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 44 publications
(68 reference statements)
0
14
0
Order By: Relevance
“…In animals, the consequences of the accumulation of HMs have been well studied, with reported effects such as oxidative stress and inflammation (e.g., Pb, Cd, and Ni) [ 62 , 63 ], changes in gene expression (e.g., Pb, Cd, and Mn) [ 64 , 65 ], destruction of the mucosa of the intestinal tract, and changes in the microbiota (e.g., Pb) [ 66 ]. Toxicity occurs through processes such as the inhibition of antioxidant enzymes, substitution of native metal ions in enzymes involved in metabolic processes, disruption of protein structures, inhibition of DNA repair, and formation of protein and/or DNA cross-links [ 60 , 67 ]. Hence, consumption of food and water contaminated by HMs can lead to serious neuronal, hepatic, renal, immunological, cardiovascular, reproductive, and gastric damage, as has been recounted in multiple studies [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…In animals, the consequences of the accumulation of HMs have been well studied, with reported effects such as oxidative stress and inflammation (e.g., Pb, Cd, and Ni) [ 62 , 63 ], changes in gene expression (e.g., Pb, Cd, and Mn) [ 64 , 65 ], destruction of the mucosa of the intestinal tract, and changes in the microbiota (e.g., Pb) [ 66 ]. Toxicity occurs through processes such as the inhibition of antioxidant enzymes, substitution of native metal ions in enzymes involved in metabolic processes, disruption of protein structures, inhibition of DNA repair, and formation of protein and/or DNA cross-links [ 60 , 67 ]. Hence, consumption of food and water contaminated by HMs can lead to serious neuronal, hepatic, renal, immunological, cardiovascular, reproductive, and gastric damage, as has been recounted in multiple studies [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Using behavioral tests, we find the in vivo performance of fullerenol can affect lead-induced-impaired learning and memory. Lead can interfere with the activities of several protein and gene expressions, so it is identified as a highly poisonous heavy metal affecting several organ systems in the body [ 23 ]. Nowadays, lead poisoning and lead pollution are mainly treated by eliminating lead [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the most likely reason for our negative experimental result was that the single doses of lead acetate administered to nestlings were too low to initiate any of the indirect mechanisms that could exert any modification in the sizes of the SSRs we analyzed. Even though the biochemical and molecular mechanisms underlying the genotoxicity of lead are not yet fully elucidated, it has been reported that lead induces a genotoxic effect throughout indirect mechanisms, such as the inhibition of DNA repair, the excess production of free radicals contributing to DNA damage, and the regulation of suppressor and promotor genes in carcinogenesis [ 8 , 12 ]. Such conclusions were assumed in one of the experimental studies conducted by [ 35 ], in which MSI was evaluated using three microsatellite loci located within the genome of rats ( Rattus norvegicus ) exposed to various heavy metal compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Lead and lead compounds have also been studied for many years in various biological systems as potential mutagenic, clastogenic, and carcinogenic agents [ 8 ]. In most clinical and/or laboratory studies of the genotoxic consequences of lead exposure conducted so far, the focus has been on several genetic endpoints as sorts of bioindicator [ 8 , 9 , 10 , 11 , 12 ]. Interestingly, relatively little attention has been paid so far to wild bird populations in this regard.…”
Section: Introductionmentioning
confidence: 99%